SINTESIS NANOPARTIKEL PERAK TERMODIFIKASI KITOSAN SEBAGAI METODE ANALISIS: REVIEW ARTIKEL - Zaki, Faisal; Yusuf, Bohari; Arif, Syaiful (PROSIDING SEMINAR KIMIA, 2024)
Silver nanoparticles themselves have been very much developed both through the method of synthesizing silver nanoparticles both physically, chemically and biologically. In the chemical method we can do by reducing Ag+ ions into silver nanoparticles which have an attachment to the reductant and also have a very strong ability to reduce Ag+ ions to become silver nanoparticles have a small size. Based on the literature review used, the reductor is Sodium Borohydrate (NaBH4). Chitosan acts as a capping agent which functions as a stabilizer in the silver nanoparticles. Silver nanoparticles modified using chitosan from previous research, namely for activity tests as antioxidants, as metal sensors and as antibacterials Where there is a change in color on silver nanoparticles from clear to yellow. Keywords: Silver Nanoparticles, Chitosan, Reducing Agent, Stabilizer, Chemical Sensor